The efficacy of Kangaroo-Mother care to the clinical outcomes of LBW and premature infants in the first 28 days: A meta-analysis of randomized clinical trials - Zhu, Zhen; Wang, Xinchen; Chen, Wenzeng; Pei, Shuping; Wang, Qingmin; Guan, Hailian; Zhu, Guang (Frontiers in Pediatrics, 2023)
The objective of this study was to construe the efficacy of Kangaroo-Mother Care (KMC) on the clinical outcomes of low birthweight (LBW) infants and preterm infants to evaluate the benefits of KMC systematically and intuitively. For this study, the following databases were retrieved for articles published from the beginning to November 2021: PubMed, Web of Science, EBSCO, and the Cochrane library. The primary clinical outcome was death between enrollment and 28 days. The secondary clinical outcomes were other relevant clinical outcomes (the mean duration of hospital stay, hypothermia, sepsis, exclusive breastfeeding at the end of the neonatal period, and exclusive breastfeeding at discharge). We conducted a meta-analysis, and the results showed that KMC could reduce the primary clinical outcome of death between enrollment and 28 days (RR: 0.80, 95% Cl: 0.71-0.91, p<0.01). For the secondary clinical outcomes, KMC had a varying degree of benefits on the mean duration of hospital stay (SMD: -0.96, 95% Cl: -1.02--0.90, p<0.001), hypothermia (RR: 0.45, 95% Cl: 0.27-0.75, p<0.01), and sepsis (RR: 0.79, 95% Cl: 0.70-0.89, p<0.001). The clinical outcomes of exclusive breastfeeding at the end of the neonatal period and exclusive breastfeeding at discharge had benefits, which was not statistically different though (RR: 1.10, 95% Cl: 0.79-1.54, p=0.58; RR: 1.25, 95% Cl: 0.79-1.96, p=0.34, respectively). KMC was beneficial to LBW infants and premature infants on the primary clinical outcome of death between enrollment and 28 days. In addition, KMC also had a favorable effect on the secondary clinical outcomes, such as mean duration of hospital stay, hypothermia, sepsis, exclusive breastfeeding at the end of the neonatal period, and exclusive breastfeeding at discharge.